Monuments to the Heroes and Victims of the World War II. Memorial Complexes of the 1960s-1970s and the Problem of Historic and Artistic Value - Smirnova, Ksenia V. (Actual Problems of Theory and History of Art, 2025)
The article highlights new trends in Soviet monumental art of the 1960–1970s, the problem of mutual influence of documental and artistic aspects of the monuments, fusion of architecture, sculpture and visual arts, their synthetic character on the whole. There is an intention to make clear, that uncritical approach to that problem leads to discredit attitude to the monuments as works of art.